Fimbrial Cells Exposure to Catalytic Iron Mimics Carcinogenic Changes. Issue 3 (1st March 2015) - Lattuada, Debora; Uberti, Francesca; Colciaghi, Barbara; Morsanuto, Vera; Maldi, Elena; Squarzanti, Diletta Francesca; Molinari, Claudio; Boldorini, Renzo; Bulfoni, Alessandro; Colombo, Paola; Bolis, Giorgio
Abstract : Objective: Recent evidence strongly suggests that the fallopian tube is a site of origin of ovarian cancer. Although histological data show iron deposition in the fallopian tubes, its role remains unclear. To establish whether catalytic iron has a possible role in ovarian carcinogenesis, we isolated human fimbrial secretory epithelial cells (FSECs). Methods: Fimbrial secretory epithelial cells, isolated from women undergoing isteroannessiectomy, were treated with different doses of catalytic iron (0.05–100 mM) to study cell viability; NO production; p53, Ras, ERK/MAPK, PI3K/Akt, Ki67, and c-Myc protein expressions through Western blot analysis; and immunocytochemistry or immunofluorescence. Results: In FSECs treated with catalytic iron for up to 6 days, we observed an increase in cell viability, NO production, and p53, pan-Ras, ERK/MAPK, PI3K/Akt, Ki67, and c-Myc activations ( P < 0.05) in a dose-dependent and time-dependent manner. These same results were also observed in FSECs maintained for respectively 2 and 4 weeks in the absence of catalytic iron after 6 days of stimulation. Conclusions: Our model aimed at studying the main nongenetic risk factor for ovarian cancer, providing an alternative interpretation for the role of menstruation in increasing risk of this pathology. This in vitro model mimics several features of the precursor lesions and opens new scenarios for further investigations regarding the correlation between damages produced by repeated retrograde menstruation carcinogenic stimuli.